Radiation Use Efficiency on the Different Varieties and the Number of Seedlings of Rice (Oryza sativa L.) - Agus Suryanto; Moch. Dawam Maghfoer; Tietyk Kartinaty (AGRIVITA, Journal of Agricultural Science, 2018)
Selection of varieties and number of seedlings per hole in rice plants is closely related to the shape of canopy, the rate of plant growth and the age of plant which determine the ability of plants to intercept and absorb solar radiation intensity. This research aimed to improve the Radiation Use Efficiency of rice by selecting plant canopies based on varieties and number of seeds per hole. Research was conducted from November 2015 to May 2016, in Landak Regency, West Kalimantan. A Split Plot Design with three replications was adopted to evaluate three varieties (Sembada-168, Inpari-30, and local varieties) as main plot, and the number of seedlings per planting hole (one, three, five, and seven seedlings per planting hole) as sub plot. Result showed that there was no interaction between varieties and the number of seedlings per hole to Radiation Use Efficiency (RUE) on rice. RUE on local variety was lower than Sembada-168 and Inpari-30. One seedling per hole had higher RUE than seven seeds with value of 3.36 and 2.17 % respectively. The number of seedlings showed that RUE of one and three seedlings per hole were higher than seven seedlings per hole.